MEDIA PEMBELAJARAN INOVATIF AUGMENTED REALITY MAJUKAN BATURETNO (DIAJARI ARJUNO) - Okvia; Nurhadi Nurhadi; Sigit Hartanto (Inisiasi, 2023)
Based on the Industrial Revolution 4.0, the utilization of technology has become mandatory for all sectors, including education. One of the applications of technology in education is the development of Augmented Reality-based learning media. Augmented Reality-based learning media is interactive and enjoyable media, thus encouraging the Regional Coordinator for Education in Baturetno District, Wonogiri Regency, Central Java, to develop the Media Pembelajaran Inovatif Augmented Reality Majukan Baturetno (DIAJARI ARJUNO). This research aims to describe and explain the benefits of the Media Pembelajaran Inovatif Augmented Reality Majukan Baturetno (DIAJARI ARJUNO). It is a qualitative descriptive research that produces data in the form of written and spoken words from observed behaviors. Data collection in this research used interview and observation techniques. From the research that has been conducted with a number of users reaching 1,620, it can be concluded that the implementation or utilization of the Media Pembelajaran Inovatif Augmented Reality Majukan Baturetno (DIAJARI ARJUNO) can attract students' attention, improve students’ motivation in learning, and enhance the variety of effective learning media that can be utilized by teachers, especially in Baturetno district.